2002
DOI: 10.1016/s0022-5347(05)65389-x
|View full text |Cite
|
Sign up to set email alerts
|

IMMUNOEXPRESSION OF p53 PROTEIN AND PROLIFERATING CELL NUCLEAR ANTIGEN IN PENILE CARCINOMA

Abstract: Proliferating cell nuclear antigen staining had no prognostic value for disease progression. Since p53 over expression was associated with tumor progression and cause specific death, perhaps it should be evaluated in staging and therapeutic planning for patients with squamous cell carcinoma of the penis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(30 citation statements)
references
References 14 publications
4
24
1
1
Order By: Relevance
“…A similar result was demonstrated by Martins et al [40], in which a positive rate of p53 correlated with T stage, histological grade, lymphatic spread, and poorer cancerspecific survival.…”
Section: Proliferative Index and Cell Cyclesupporting
confidence: 86%
See 1 more Smart Citation
“…A similar result was demonstrated by Martins et al [40], in which a positive rate of p53 correlated with T stage, histological grade, lymphatic spread, and poorer cancerspecific survival.…”
Section: Proliferative Index and Cell Cyclesupporting
confidence: 86%
“…Basaloid carcinomas showed higher proliferation index than verrucous carcinoma. Previously, Martins et al [40] associated high proliferative index as measured by PCNA with the likelihood of developing lymph node metastasis, but were unable to correlate their findings with histological grade. Guimaraes et al [41] showed that the high proliferative index (over 50% of stained cells) measured by PCNA strongly correlated with lymph node metastasis in univariate analysis, but it was not an independent factor for recurrence and survival.…”
Section: Proliferative Index and Cell Cyclementioning
confidence: 90%
“…348 Pelvic lymph nodes involvement has a worse prognosis, with a 5-year survival of less than 5%. 330 Other predictors of a higher risk of tumor progression include the depth of infiltration of the primary tumor, the presence of vascular invasion, 358 the degree of cell differentiation, 359 and p53 overexpression in tumoral tissue, 360,361 whereas the presence of HPV infection does not seem to be of any prognostic value. 362,363 After treatment, patients with penile carcinoma should be adequately followed up for at least 3 years to promptly detect any relapses, which occur mostly during the first 12 to 18 months after diagnosis.…”
Section: Prognosismentioning
confidence: 99%
“…Expression of p53 is closely related to p16 expression (p21 pathway), and expression of both tumor suppressor genes is partly influenced by the same regulators [1,2]. Since strong expression of p53 has been shown to be associated with metastasis and poor prognosis in penile carcinomas [36,37], we additionally examined the expression of p53, searched for allelic losses and mutations in the p53 gene, and compared p53 expression to HPV status, LOH in 9p21, and p16 expression.…”
Section: Discussionmentioning
confidence: 99%